MULTICRITERIA ANALYSIS FOR PROJECT PORTFOLIO EVALUATION APPLIED TO RESEARCH PROJECTS AND DEVELOPMENT BIOEN FOR STAGE AGRICULTURAL - Lamarca, D. S. F.; Magalhães, M. M.; Braga Junior, S. S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
This study aims to provide inputs for evaluating the performance of portfolios of projects of R & D Research Program on Bioenergy (BIOEN), the Support Foundation of São Paulo (FAPESP), using methods of supporting research to multi-criteria decision-making processes in project evaluation. A combination of methodologies for the assessment of project portfolio through adaptation practices already established in the market and research in terms of R & D project management is necessary. Thus, this research took place one multi-criteria analysis to organize projects in portfolios (types of projects) related to the agricultural stage. Using the methodology of multi-criteria analysis, an electronic questionnaire was sent to experts in the field. Thus, with the collected responses were prepared five portfolios of projects related to agricultural second generation step of the ethanol production process. As a contribution, the formations of these portfolios generate information for decision-making processes in the business plan (investments), which can be used to BIOEN products and processes.